Real-time calcium uptake monitoring of a single renal cancer cell based on an all-solid-state potentiometric microsensor - Zhai, Jiali; Wang, Wenting; Wu, Shuang; Yu, Tianxi; Xiang, Chongjun; Li, Yue; Lin, Chunhua; Zhao, Guangtao (Frontiers in Bioengineering and Biotechnology, 2023)
Besides in many cellular processes, Ca2+ is also involved in tumor initiation, progression, angiogenesis, and metastasis. The development of new tools for single-cell Ca2+ measurement could open a new view in cancer therapy. The proposed all-solid-state calcium ion-selective microelectrode (Ca2+-ISμE) based on carbon fiber modified with PEDOT/PSS exhibits a stable Nernstian response in CaCl2 solutions in the active range of 1.0 × 10-8 - 3.1 × 10-3 M with a low detection limit of 8.9 × 10-9 M. The Ca2+-ISμE can be connected to patch clamp to fabricate single-cell analysis platform for in vivo calcium monitoring of single renal carcinomas cell. The calcium signal decreased significantly (8.6 ± 3.2 mV, n=3) with sever fluctuations of 5.9 ± 1.8 mV when the concentration of K+ in tumor microenvironment is up to 20 mM, which indicates a sever cell response under high K+ stimuli. The detection system could also be used for single-cell analysis of other ions through changing different ion-selective membranes with high temporal resolution.